Conflict Management and Organizational Behavior: Principal Strategies - Luqman, Kharis; Rodliyah, St.; Fatmawati, Erma (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Letiges & Association of Muslim Community in ASEAN (AMCA), 2024)
This study aims to explore conflict management strategies and organizational behaviour within educational institutions, specifically focusing on the role of school principals in addressing conflicts between teachers and staff. The research addresses the pressing need for effective conflict resolution in school environments to uphold organizational goals and foster a conducive learning atmosphere. Employing a qualitative approach with a descriptive design, the study utilizes observation, interviews, and documentation as primary data collection methods. Through direct observation and interviews with key stakeholders, the research delves into the intricacies of conflict resolution strategies employed by school principals. The study identifies conflicts between teachers and educational staff stemming from disputes over values, interests, and perceptions. Principals adopt collaborative strategies, including coaching and mediation, to resolve conflicts and promote mutual understanding among conflicting parties. However, resistance from individuals driven by personal agendas hinders conflict resolution efforts. Limitations are acknowledged, particularly in areas with restricted technologies, such as some educational institutions in developing countries. These limitations may affect the implementation of conflict resolution strategies and organizational behavior management. This study contributes to the literature by providing insights into effective conflict management strategies within educational settings. By highlighting the pivotal role of school principals and exploring innovative approaches to conflict resolution, the research offers practical implications for enhancing organizational dynamics in schools. Future research could further explore the impact of cultural and contextual factors on conflict management strategies and investigate novel approaches to mitigate conflict in diverse educational contexts.